Singular adverb (Al-Hal) in Ibn Atia’s book (Al- Moharir Al- Wageeze Fe Al- kitab Al- Aziz): Surah Al-Baqarah as an example - Al-Mihimdi, Hasan Hadi Fadhil (Journal of Arabic Language Sciences and Literature, 2022)
In this research, we tried to stand on the adverb placements which ibn atia mentioned in (Al- Moharrir Al- Wageeze) and specifically in Surah Al-Baqarah by supporting it with the previous grammarians and explainers, opinions. This research is divided into one part, the first one deals with the adverb of a single word, this research started with an introduction, explanation, conclusion and finally ended with the results. Also, in this research we have to say that all the scholars and the researchers have no way to do in front of the holy Quran and they will not be able to discover all its secrets and its implied meanings. One of the most important results in this research is that the meaning has a great impact on (adverb) and the advantages of the adverb may be inserted inside the meaning. We hope that the readers got an adventage from this simple research.